Quantitative study of optical and mechanical bone status using multispectral photoacoustics. Issue 9 (21st October 2015) - Steinberg, Idan; Turko, Nir; Levi, Omri; Gannot, Israel; Eyal, Avishay
Abstract : Osteoporosis is a major public health problem worldwide. Here, we present a quantitative multispectral photoacoustic method for the evaluation of bone pathologies which has significant advantages over pure ultrasonic or pure optical methods as it provides both molecular information and bone mechanical status. This is enabled via a simultaneous measurement of the bone's optical properties as well as the speed of sound and ultrasonic attenuation in the bone. To test the method's quantitative predictions, a combined ultrasonic and photoacoustic system was developed. Excitation was performed optically via a portable triple laser‐diode system and acoustically via a single element transducer. Additional dual transducers were used for detecting the acoustic waves that were generated by the two modalities. Both temporal and spectral parameters were compared between different excitation wavelengths and measurement modalities. Short photoacoustic excitation wavelengths allowed sensing of the cortical layer while longer wavelengths produced results which were compatible with the quantitative ultrasound measurements. Abstract : A multi‐spectral photoacoustic method based on low‐cost laser diodes is presented for evaluation of bone pathologies. Such method has significant advantage over pure ultrasonic or optical methods as it provides both molecular information and bone mechanical status. Both time and frequency domain analysis sheds light on the interaction of light and sound with the bone. The photoacoustic method is compared to a clinically accepted quantitative ultrasound and its clinical value is presented.